Current methodologies for a sustainable approach to π-conjugated organic semiconductors. Issue 3 (21st January 2016) - Marrocchi, Assunta; Facchetti, Antonio; Lanari, Daniela; Petrucci, Chiara; Vaccaro, Luigi
Abstract : The development of waste minimized and clean synthetic methodologies to afford polymeric semiconductors is essential for the successful commercialization of opto-electronic devices. Abstract : The most effective synthetic methodologies currently employed for producing polymeric semiconductors are affected by cost, safety, and environmental issues which may seriously prevent their large-scale production. In this regard, the application of principles of green chemistry for the development of waste-minimized and cleaner synthetic approaches to semiconductor synthesis is essential for propelling the field of organic electronics. In this review, selected advances in the development of synthetic green strategies for the preparation of poly(arylene) families as well as their implication in the performance of selected opto-electronic devices such as organic thin-film transistors and bulk heterojunction solar cells are summarized.